2017
DOI: 10.1371/journal.pone.0176038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating dispersal potential of an invasive fish by the use of aerobic scope and osmoregulation capacity

Abstract: Non-indigenous species (NIS) can impact marine biodiversity and ecosystem structure and function. Once introduced into a new region, secondary dispersal is limited by the physiology of the organism in relation to the ambient environment and by complex interactions between a suite of ecological factors such as presence of predators, competitors, and parasites. Early prediction of dispersal potential and future ‘area of impact’ is challenging, but also a great asset in taking appropriate management actions. Aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 97 publications
3
63
3
Order By: Relevance
“…Thriving in brackish and fresh water (Demchenko & Tkachenko, ), it has been speculated that high salinity provides a dispersal barrier for the species as it approaches the North Sea (Kornis et al., ). Yet, a study revealed that slow acclimation to increasing salinities enables high survival of adults and only marginally reduces physiological performance at salinities as high as 30 psu (Behrens, van Deurs & Christensen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thriving in brackish and fresh water (Demchenko & Tkachenko, ), it has been speculated that high salinity provides a dispersal barrier for the species as it approaches the North Sea (Kornis et al., ). Yet, a study revealed that slow acclimation to increasing salinities enables high survival of adults and only marginally reduces physiological performance at salinities as high as 30 psu (Behrens, van Deurs & Christensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a study revealed that slow acclimation to increasing salinities enables high survival of adults and only marginally reduces physiological performance at salinities as high as 30 psu (Behrens, van Deurs & Christensen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most wide‐ranging invasive species of fresh‐ and brackish‐water environments is the round goby Neogobius melanostomus (Pallas) (Kornis, Mercado‐Silva, & Vander Zanden, ) . Originating from the Ponto–Caspian region, the round goby is a highly successful invader of novel environments (Behrens, van Deurs, & Christensen, ; Nurkse, Kotta, Orav‐Kotta, & Ojaveer, ), with established populations in the North American Great Lakes, the Baltic Sea and many European rivers (Jude, Reider, & Smith, ; Azour et al, ; Buřič, Bláha, Kouba & Drozd, ; Kotta, Nurkse, Puntila, & Ojaveer, ). The round goby feeds heavily on bivalves, both in its native (Skazkina & Kostyuchenko, ) and invaded ranges (Järv, Kotta, Kotta, & Raid, ; Raby, Gutowsky, & Fox, ).…”
Section: Mean Total Length (Tl ± Se) In CM Of Round Goby Size Groups mentioning
confidence: 99%
“…for unperturbed osmoregulation(Behrens et al 2017). However, the round goby's repertoire of key-719 genes in myo-inositol production and accumulation might bestow the species with the potential to 720 eventually tolerate higher salinities, for example through the evolution of altered gene regulation 721 patterns, and colonize higher PSUs.…”
mentioning
confidence: 99%